Validating a port simulation model with application to the port of Alexandria, Egypt. (13th October 2010) - Ragheb, Mohamed Abdel Salam; Rekab, Kamel; Tadj, Lotfi
In this paper we first review the key literature on seaport simulation and simulation model validation techniques. Then we study the validation of a seaport simulation model, namely the port of Alexandria, Egypt. One of the most important techniques is to build a regression metamodel that represents the relationship between the model inputs and model outputs. We prove that the simulation model is valid. The output of this study is a decision-support model that will form the base of a decision-support system that can be used by management to improve the decision-making process.